THE EFFECT OF PROFITABILITY, LIQUIDITY AND CORPORATE GOVERNANCE ON PROFIT QUALITY IN FOOD AND BEVERAGE SUB-SECTOR COMPANIES THAT LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2023 - Pratiwi, Iis; Sahmin Noholo; Nilawaty Yusuf (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to identify and analyze the influence of profitability, liquidity, and corporate governance on the quality of profits. This research was conducted on the food and beverage sub-sector listed on the Indonesia Stock Exchange in the 2019-2023 period using a quantitative approach. The sample determination was carried out by the purposive sampling method, resulting in a total of 12 companies observed over a period of 5 years, so that the total sample used was 60. Data analysis was carried out using the SPSS 26 program. The results showed that profitability, audit committees, and institutional ownership had a significant effect on the quality of profits, while liquidity and independent commissioners did not show a significant influence. However, simultaneously, all of these variables have a significant effect on the quality of profit.